Shear strengthening of reinforced concrete beams using externally-bonded aluminum alloy plates: An experimental study - Abdalla, Jamal A.; Abu-Obeidah, Adi S.; Hawileh, Rami A.; Rasheed, Hayder A. (My University, 2016)
Recently developed high strength aluminum alloys (AA) have desirable characteristics that make them attractive as externally bonded strengthening materials. This paper investigates the potential of using AA plates for shear strengthening of reinforced concrete (RC) beams. Five shear deficient RC beams were externally strengthened using AA plates with different orientations. It is observed that the shear capacity of the strengthened beams has increased in the range of 24%–89% compared to the un-strengthened beam. Shear capacity of the strengthened beams was also predicted using the ACI440, FIB14, TR55 and SMCFT design guidelines with the later one giving the most accurate predictions.
Citation: Jamal A. Abdalla, Adi S. Abu-Obeidah, Rami A. Hawileh, Hayder A. Rasheed, Shear strengthening of reinforced concrete beams using externally-bonded aluminum alloy plates: An experimental study, Construction and Building Materials, Volume 128, 15 December 2016, Pages 24-37 http://dx.doi.org/10.1016/j.conbuildmat.2016.10.071
Keywords: Aluminum alloy; Externally-bonded material; Shear deficient beams; Fiber Reinforced Polymer (FRP)